2021
DOI: 10.1109/toh.2021.3085756
|View full text |Cite
|
Sign up to set email alerts
|

Impact Vibration Source Localization in Two-Dimensional Space Around Hand

Abstract: This study investigated the localization ability of an impulse vibration source outside the body in two-dimensional space. We tested whether humans can recognize the direction or distance of an impulse vibration source when using their hand to detect spatiotemporal vibrotactile information provided by the propagated vibrational wave from the source. Specifically, we had users put their hands on a silicone rubber sheet in several postures. We asked users to indicate the position of the vibration source when a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 39 publications
(47 reference statements)
2
22
2
Order By: Relevance
“…With this method, the user needs to recognize the direction and distance of a remote vibration source based on the propagated vibration. We have investigated the accuracy of source localization with an impact vibration, and found that the direction could be recognized to some extent, but the distance could not be recognized accurately (Ujitoko et al, 2021). Based on the same idea as that proposed in our previous study (Ujitoko et al, 2021), the present study investigates the accuracy of source localization but this time using a sinusoidal vibration due to following reasons.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…With this method, the user needs to recognize the direction and distance of a remote vibration source based on the propagated vibration. We have investigated the accuracy of source localization with an impact vibration, and found that the direction could be recognized to some extent, but the distance could not be recognized accurately (Ujitoko et al, 2021). Based on the same idea as that proposed in our previous study (Ujitoko et al, 2021), the present study investigates the accuracy of source localization but this time using a sinusoidal vibration due to following reasons.…”
Section: Introductionmentioning
confidence: 86%
“…We have investigated the accuracy of source localization with an impact vibration, and found that the direction could be recognized to some extent, but the distance could not be recognized accurately (Ujitoko et al, 2021). Based on the same idea as that proposed in our previous study (Ujitoko et al, 2021), the present study investigates the accuracy of source localization but this time using a sinusoidal vibration due to following reasons. First, voice-coil motors, which are usually used to simulate sinusoidal vibrations, are a better option for tactile presentation than solenoids, which are usually used to simulate impulse vibrations, in the following three ways: power consumption (see Immersion, 2020), heat, and controllability (see Choi and Kuchenbecker, 2012).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations